ATM MONITORING WITH RADIO CALL - Niken Indreswari; Ir. Susi W, MM Ir. Susi W, MM (Jurnal Sistem Informasi, 1997)
Communications technology today has progressed very rapidly. Various kinds of communication devices participate in supporting the achievement of these advances in communications technology. Ease in communication, can now be felt by us, especially the radio wave communications. Beeper (pager) is one result of advances in communications technology using radio waves used for the delivery of messages. But now the radio call (pager) have been used as a medium of message delivery in the areas of financial business. Monitoring the success of the transaction at ATMs (Automatic Teller Machine) is expected by each user of the ATM machine, all the mistakes that occurred must immediately known. For that ATM with the Radio Call Monitoring is one step in streamlining the functions of its own ATM machine. In writing this thesis, the author will give an explanation of how the ATM with the Radio Call Monitoring runs. The ingredients are already used by Page. BANK BALI in monitoring the effectiveness of ATM function optimally.